2005
DOI: 10.1128/aem.71.9.5324-5331.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Persistent, Productive, and Seasonally Dynamic Vibriophage Population within Pacific Oysters ( Crassostrea gigas )

Abstract: In an effort to understand the relationship between Vibrio and vibriophage populations, abundances of Vibrio spp. and viruses infecting Vibrio parahaemolyticus (VpVs) were monitored for a year in Pacific oysters and water collected from Ladysmith Harbor, British Columbia, Canada. Bacterial abundances were highly seasonal, whereas high titers of VpVs (0.5 ؋ 10 4 to 11 ؋ 10 4 viruses cm ؊3 ) occurred year round in oysters, even when V. parahaemolyticus was undetectable (<3 cells cm ؊3 ). Viruses were not detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Eighteen of the 22 isolated phages showed unique host ranges of infectivity against 24 strains of F. psychrophilum, which all had unique phage susceptibility patterns. This high phage and host diversity within the Flavobacterium psychrophilum group supports recent studies of Cellulophaga baltica (13), Vibrio parahaemolyticus (6,7), and E. coli (e.g., references 10 and 24) and indicates that interactions between F. psychrophilum and their phages are characterized by a high degree of complexity at the strain level. The facts that phages were found in more than 50% of the analyzed samples and that 18 of 22 F. psychrophilum phage isolates were unique with respect to host range suggested that the obtained phage isolates most likely represent only a small fraction of the actual F. psychrophilum phage diversity in aquaculture.…”
Section: Figsupporting
confidence: 61%
“…Eighteen of the 22 isolated phages showed unique host ranges of infectivity against 24 strains of F. psychrophilum, which all had unique phage susceptibility patterns. This high phage and host diversity within the Flavobacterium psychrophilum group supports recent studies of Cellulophaga baltica (13), Vibrio parahaemolyticus (6,7), and E. coli (e.g., references 10 and 24) and indicates that interactions between F. psychrophilum and their phages are characterized by a high degree of complexity at the strain level. The facts that phages were found in more than 50% of the analyzed samples and that 18 of 22 F. psychrophilum phage isolates were unique with respect to host range suggested that the obtained phage isolates most likely represent only a small fraction of the actual F. psychrophilum phage diversity in aquaculture.…”
Section: Figsupporting
confidence: 61%
“…Although these methods work well for comparing total bacteria and total phage numbers in a given environment, they provide no data regarding specific phage-host interactions. For that purpose, one must isolate and study specific phagehost systems, as was done in this study and in a small number of other studies covering shorter time periods (Hantula et al, 1991;Comeau et al, 2005;Clokie et al, 2006). As phage abundance depends on the concentration of its specific host, it is preferable to isolate strains that are sufficiently dominant in the studied environment.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio phages are typically speciesspecific, and often strain-specific (Comeau et al, 2005), and experiments have shown undetectable binding of PWH3a-P1 to natural populations of bacteria, even in the environment from which it was isolated (Hennes et al, 1995). Finally, even if PWH3a-P1 were able to bind to Vibrio spp., the estimated abundance of Vibrio spp.…”
Section: Remineralisation Of Nitrogen In Bacterial Lysatesmentioning
confidence: 99%